2019
DOI: 10.1055/s-0039-1685156
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Tongue Base Reduction and Lingual Tonsillectomy for Residual Pediatric Obstructive Sleep Apnea after Adenotonsillectomy

Abstract: Introduction  Upper airway obstruction at multiple sites, including the velum, the oropharynx, the tongue base, the lingual tonsils, or the supraglottis, has been resulting in residual obstructive sleep apnea (OSA) after tonsillectomy and adenoidectomy (TA). The role of combined lingual tonsillectomy and tongue base volume reduction for treatment of OSA has not been studied in nonsyndromic children with residual OSA after TA. Objective  To evaluate the outcomes of tongue base volume reduction and lingual tons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Evidence supporting this can be found in the study by Park et al, 85 which demonstrated a significant improvement in OSA‐18 QOL scores in children with hypotonia after DISE‐directed surgery. Subjectively, DISE‐directed surgery has also been found to improve patient‐reported symptoms such as snoring, pauses in breathing, gasping for air, mouth breathing, daytime somnolence, sleepwalking, sleep talking, teeth grinding, enuresis, and feeling tired 87 . Future prospective studies on pediatric DISE‐directed surgery should include validated QOL and symptom scores when assessing outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence supporting this can be found in the study by Park et al, 85 which demonstrated a significant improvement in OSA‐18 QOL scores in children with hypotonia after DISE‐directed surgery. Subjectively, DISE‐directed surgery has also been found to improve patient‐reported symptoms such as snoring, pauses in breathing, gasping for air, mouth breathing, daytime somnolence, sleepwalking, sleep talking, teeth grinding, enuresis, and feeling tired 87 . Future prospective studies on pediatric DISE‐directed surgery should include validated QOL and symptom scores when assessing outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Subjectively, DISE-directed surgery has also been found to improve patient-reported symptoms such as snoring, pauses in breathing, gasping for air, mouth breathing, daytime somnolence, sleepwalking, sleep talking, teeth grinding, enuresis, and feeling tired. 87 Future prospective studies on pediatric DISE-directed surgery should include validated QOL and symptom scores when assessing outcomes.…”
Section: Outcomes Of Dise-directed Surgerymentioning
confidence: 99%
“… 40 And craniofacial or dentoalveolar aesthetics of patients with Trisomy 21 can be improved with surgical procedures and orthodontic treatments. 35 , 41 …”
Section: The Physiological Growth and Developmental Anomalied Of Nerv...mentioning
confidence: 99%
“…Similar to our findings, previous studies documented upper airway obstruction due to the tongue or epiglottis in surgically naïve children with OSA as well as in children with residual OSA. 18,19 Drug-induced sleep endoscopy facilitates targeted surgical approaches and individualized surgical treatments while avoiding failures after TA. 18,[20][21][22][23][24][25] The use of DISE at the time of TA in surgically naïve infants and children with OSA altered the surgical decision making in 35% of infants and in 24% of older children.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, previous studies documented upper airway obstruction due to the tongue or epiglottis in surgically naïve children with OSA as well as in children with residual OSA. 18 19…”
Section: Discussionmentioning
confidence: 99%